Prospects, Status and Development of Internet Banking in India - Dr. Chitranjan Singh (International Journal of Engineering and Management Research, 2019)
Internet banking’s contribution to economic development is becoming increasingly important in emerging countries like India. The conventional banking system is being replaced by a virtual one, as banks no longer rely solely on it. The use of information technology in banking has made the banking experience more pleasant for customers. There has been an increase in the use of information technology in banking operations, which has resulted in better customer service. Customers can access banking services without having to visit a bank location. There is now a shift from the old mode of service to ATMs, Internet banking, and mobile banking, as well as IT-enabled services. Through internet banking, banks are focusing on value-based service. A look at the rise of Internet banking and the products that are being used in the banking sector is the focus of this study.